2016
DOI: 10.18666/jasm-2016-v8-i4-7221
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Women’s Sports Fans’ Attitudes and Consumption Intentions

Abstract: To date, few studies have focused on understanding fans of women's sport, which is especially true with regard to consumption intentions. This study was undertaken to 1) examine fans' attitudes toward women's sports, including both cognitive and affective evaluations as related to consumption intentions; 2) identify salient product attributes of women's sports related to fans' consumption intentions; and 3) examine group differences on attitudes. Multiple regression analysis and multivariate analysis of varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Conversely, the LGBTQ þ group showed significantly lower mean scores on all eight subscales than all three marginalized groups examined. This supports Mumcu and Lough (2017) suggestions to incorporate marketing strategies that are designed with authentic consideration of consumer identity. Furthermore, when compared to the LGBTQ þ group, the intersectional dual identity group had significantly higher means scores on aesthetics, drama, and escape.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Conversely, the LGBTQ þ group showed significantly lower mean scores on all eight subscales than all three marginalized groups examined. This supports Mumcu and Lough (2017) suggestions to incorporate marketing strategies that are designed with authentic consideration of consumer identity. Furthermore, when compared to the LGBTQ þ group, the intersectional dual identity group had significantly higher means scores on aesthetics, drama, and escape.…”
Section: Discussionsupporting
confidence: 63%
“…Specifically, in a scoping review examining the state of diversity in sport consumer research, Delia et al (2022) found only one of the 535 articles reviewed disclosed information about sexual orientation. In that study, Mumcu and Lough (2017) investigated heterosexual and LGBT consumer attitudes towards a WNBA Pride campaign. Results showed that while LGBT participants expressed more positive evaluations of the campaign, the promotion did not construct a negative effect on heterosexual spectators.…”
Section: Sexual and Gender Identity And Marginalization In Sportmentioning
confidence: 99%
“…Measures: Engagement with the team is measured using five items adapted from Dwyer (2013) and Mumcu et al (2016). Intention to purchase team merchandise is measured by Lee et al's (2013) 3-item scale.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Measures : Engagement with the team is measured using five items adapted from Dwyer (2013) and Mumcu et al. (2016).…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Finally, there is a complete lack of studies on the commercialization of women's elite sports and its impacts on its fans in this review (Table 3). This should be addressed given the rapid increase in commercial influences in women's elite sports (Meier and von Uechtriz, 2020;Mumcu et al, 2016). Thus, there is an urgency in approaching fans of women's elite sports and discussing how they respond to commercialization.…”
Section: Diversity Of Commercializationmentioning
confidence: 99%